2018
DOI: 10.1186/s40001-017-0299-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine ligand–receptor interactions critically regulate cutaneous wound healing

Abstract: BackgroundWound healing represents a dynamic process involving directional migration of different cell types. Chemokines, a family of chemoattractive proteins, have been suggested to be key players in cell-to-cell communication and essential for directed migration of structural cells. Today, the role of the chemokine network in cutaneous wound healing is not fully understood. Unraveling the chemokine-driven communication pathways in this complex process could possibly lead to new therapeutic strategies in woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 37 publications
(38 reference statements)
3
29
2
Order By: Relevance
“…43 M2 macrophages release a myriad of factors (eg, transforming growth factor-b1) to promote reepithelialization, fibroplasia, fibroblast differentiation, 13 and ECM remodeling. 29 In the current study, it is shown, for the first time, that iron treatment of macrophages significantly potentiated the release of a range of chemokines, which promoted collagen production in HDFs. M2 macrophage CM is known to stimulate collagen 1 and collagen 3 production in fibroblasts in vitro, 44 but direct application of M2-stimulated BMDMs did not alter Db healing in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…43 M2 macrophages release a myriad of factors (eg, transforming growth factor-b1) to promote reepithelialization, fibroplasia, fibroblast differentiation, 13 and ECM remodeling. 29 In the current study, it is shown, for the first time, that iron treatment of macrophages significantly potentiated the release of a range of chemokines, which promoted collagen production in HDFs. M2 macrophage CM is known to stimulate collagen 1 and collagen 3 production in fibroblasts in vitro, 44 but direct application of M2-stimulated BMDMs did not alter Db healing in vivo.…”
Section: Discussionmentioning
confidence: 52%
“…135 The keratinocyte-derived CCL20 in autocrine or paracrine manner binds CCR6 and upregulates migratory capacity of keratinocytes that may accelerate the Koebner phenomenon in psoriatic patients. 135 In IL-4/IL-13dominant AD, pruritus-mediated scratching induces CCL20 production from epidermal keratinocytes, which may explain why IL-17A-producing immune cells infiltrate atopic skin. However, the pathogenic role of IL-17A-producing immune cells in AD may be limited.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we noticed that LR pairs involved in wound healing regulation (54) were expressed by IFE K2 and D1 (Fig. 4I).…”
Section: Mouse Interfollicular Epidermis Applicationmentioning
confidence: 91%